Neorogioltriol and Related Diterpenes from the Red Alga Laurencia Inhibit Inflammatory Bowel Disease in Mice by Suppressing M1 and Promoting M2-Like Macrophage Responses - Maria G. Daskalaki; Dimitra Vyrla; Maria Harizani; Christina Doxaki; Aristides G. Eliopoulos; Vassilios Roussis; Efstathia Ioannou; Christos Tsatsanis; Sotirios C. Kampranis (Marine Drugs, 2019)
Macrophages are central mediators of inflammation, orchestrating the inflammatory response through the production of cytokines and nitric oxide. Macrophages obtain pro-inflammatory (M1) and anti-inflammatory (M2) phenotypes, which can be modulated by soluble factors, including natural products. Despite the crucial protective role of inflammation, chronic or deregulated inflammation can lead to pathological states, such as autoimmune diseases, metabolic disorders, cardiovascular diseases, and cancer. In this case, we studied the anti-inflammatory activity of neorogioltriol (1) in depth and identified two structurally related diterpenes, neorogioldiol (2), and O11,15-cyclo-14-bromo-14,15-dihydrorogiol-3,11-diol (3), with equally potent activity. We investigated the mechanism of action of metabolites 1⁻3 and found that all three suppressed macrophage activation and promoted an M2-like anti-inflammatory phenotype by inducing expression of Arginase1, MRC1, IRAK-M, the transcription factor C/EBPβ, and the miRNA miR-146a. In addition, they suppressed iNOS induction and nitric oxide production. Importantly, treatment of mice with 2 or 3 suppressed DSS-induced colitis by reducing tissue damage and pro-inflammatory cytokine production. Thus, all these three diterpenes are promising lead molecules for the development of anti-inflammatory agents targeting macrophage polarization mechanisms.